Amphibian areas of endemism: A conservation priority in the threatened Mexican cloud forest - Gustavo Montiel Canales; Irene Goyenechea Mayer Goyenechea (Vertebrate Zoology, 2022)
Amphibians of the Mexican Cloud Forest have a great diversity but are highly threatened. Forest endemisms are useful for recognizing biodiversity hotspots; furthermore, the interaction of historical and current events has generated areas of endemism that can be used for biological conservation in forest fragments; therefore, their identification is an essential part of the management and planning of biological conservation. Thus, our objective was to identify areas of endemism in the cloud forests of Mexico through the analysis of geographical distribution of 126 species of amphibians, as well as their conservation status to obtain information that supports the selection of priority areas for conservation. For this, the endemicity analysis method was used with three spatial scales, 1°×1°, 0.5°×0.5° and 0.25°×0.25° (lat/long), to achieve more complete results and avoid visual overrepresentation of areas of endemism. Seventeen consensus areas distributed in four of the five provinces of the Mexican Transition Zone were identified. The province of the Sierra Madre del Sur exhibited the highest amount of endemism areas, followed by the Sierra Madre Oriental, the East of the Trans-Mexican Volcanic Belt, and the Altos de Chiapas. Results indicate that the endemic areas of the Sierra Madre Oriental and Sierra Madre del Sur provinces are composed of amphibians included in the IUCN red list and the Official Mexican Standard NOM-059. Thus, the small areas of endemism in eastern and western Sierra Madre del Sur, nested within larger ones may be used to increase the protected areas of cloud forests in Mexico.